Scaffold morphing leading to evolution of 2, 4-diaminoquinolines and aminopyrazolopyrimidines as inhibitors of the ATP synthesis pathway12. Issue 5 (31st March 2016) - Tantry, Subramanyam J.; Shinde, Vikas; Balakrishnan, Gayathri; Markad, Shankar D.; Gupta, Amit K.; Bhat, Jyothi; Narayan, Ashwini; Raichurkar, Anandkumar; Jena, Lalit Kumar; Sharma, Sreevalli; Kumar, Naveen; Nanduri, Robert; et al.
Abstract : 2, 4-Diaminoquinazolines, 2, 4-diaminoquinolines and aminopyrazolopyrimidines, inhibitors of mycobacterial ATP synthesis, are novel lead molecules towards discovery and development of new anti-tubercular agents. Abstract : The success of bedaquiline as an anti-tubercular agent for the treatment of multidrug-resistant tuberculosis has validated the ATP synthesis pathway and in particular ATP synthase as an attractive target. However, limitations associated with its use in the clinic and the drug–drug interactions with rifampicin have prompted research efforts towards identifying alternative ATP synthesis inhibitors with differentiated mechanisms of action. A biochemical assay was employed to screen AstraZeneca's corporate compound collection to identify the inhibitors of mycobacterial ATP synthesis. The high-throughput screening resulted in the identification of 2, 4-diaminoquinazolines as inhibitors of the ATP synthesis pathway. A structure–activity relationship for the quinazolines was established and the knowledge was utilized to morph the quinazoline core into quinoline and pyrazolopyrimidine to expand the scope of chemical diversity. The morphed scaffolds exhibited a 10-fold improvement in enzyme potency and over 100-fold improvement in selectivity against inhibition of mammalian mitochondrial ATP synthesis. These novel compounds were bactericidal and demonstrated growth retardation of Mycobacterium tuberculosis in the acute mouse model of tuberculosis infection.